2016
DOI: 10.1016/j.ajhg.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Truncating Mutations in TANGO2 Cause Infancy-Onset Recurrent Metabolic Crises with Encephalocardiomyopathy

Abstract: Molecular diagnosis of mitochondrial disorders is challenging because of extreme clinical and genetic heterogeneity. By exome sequencing, we identified three different bi-allelic truncating mutations in TANGO2 in three unrelated individuals with infancy-onset episodic metabolic crises characterized by encephalopathy, hypoglycemia, rhabdomyolysis, arrhythmias, and laboratory findings suggestive of a defect in mitochondrial fatty acid oxidation. Over the course of the disease, all individuals developed global br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(147 citation statements)
references
References 11 publications
6
141
0
Order By: Relevance
“…The variants were absent or extremely rare (<0.002%) in the gnomAD database, and homozygous carriers were lacking. In three European families without known consanguineous descent (families 1, 5, and 7), five patients were homozygous for the previously described approximately 34‐kb deletion encompassing exons 3 to 9, likely reflecting an ancestral variant in Europeans . Population‐based studies have shown that heterozygous loss of this region is found in white Europeans with an allele frequency of between 0.062% and 0.11%, with homozygous deletions being absent in large control datasets.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The variants were absent or extremely rare (<0.002%) in the gnomAD database, and homozygous carriers were lacking. In three European families without known consanguineous descent (families 1, 5, and 7), five patients were homozygous for the previously described approximately 34‐kb deletion encompassing exons 3 to 9, likely reflecting an ancestral variant in Europeans . Population‐based studies have shown that heterozygous loss of this region is found in white Europeans with an allele frequency of between 0.062% and 0.11%, with homozygous deletions being absent in large control datasets.…”
Section: Discussionmentioning
confidence: 54%
“…Not fully compatible with this notion, a subsequent study found mouse Tango2 (also known as T10) to carry a conserved N‐terminal leader sequence that directs it to the mitochondrial compartment . Clinical resemblance between TANGO2 ‐related disease and fatty acid oxidation disorders such as carnitine palmitoyltransferase II (CPT2) deficiency, led to the speculation that TANGO2 may play a direct role in mitochondrial beta‐oxidation . In light of this we revisited the subcellular distribution of TANGO2.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations